Nagiyev, Nizami - (:unkn) unknown (My University, 2026)
Nizami Hasan Nagiyev, Doctor of Architecture, graduated in 1967 with a degree in Architecture from the Faculty of Urban Planning of the Leningrad Civil Engineering Institute (now Saint Petersburg, Russia). From 1969 to 1972, he pursued postgraduate studies at the Central Research Institute of Urban Planning in Moscow, Russia, and was awarded the degree of Candidate of Architecture in 1974. In 2011, he earned the degree of Doctor of Architecture after successfully defending his doctoral dissertation. Since 1996, he has been a faculty member at the Azerbaijan University of Architecture and Construction (AzUAC). He has served as the Head of the Department of Fundamentals of Architecture since 2001. In 2025, he was awarded the Presidential Individual Scholarship by the President of the Republic of Azerbaijan. Professor Nagiyev is the author of master plans for numerous cities and settlements in Azerbaijan, more than 100 architectural and construction projects, over 20 research projects, more than 50 scientific publications, three monographs, as well as several textbooks, teaching manuals, and academic curricula.